POLIMORFISME PEROKSIDASE RAMIN (Gonystylus bancanus (Miq.) Kurz) DI HUTAN PT. DIAMOND RAYA TIMBER PROVINSI RIAU - Mellyasari Pangkey; Ninik Nihayatul Wahibah; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ramin is a peat swamp endemic plant highly demanded in furniture industries. The high price and market demand has led to increase the illegal logging which subsequently threaten ramin population existence. On the other hand, genetic related information on ramin is limited. Biochemical approaches such as isozyme can be used to analyze genetic diversity. The objective of this study was to reveal the peroxsidase (PER) polimorphism of ramin natural population at PT. Diamond Raya Timber (PT. DRT) forest in Riau Province. PER were analyzed using horizontal elektrophoresis model. The leaf samples that used in this study were collected from 50 individuals ramin. Data were analyzed using SAHN function and UPGMA method by NTSYS version 2.0. The results showed that PER enzyme produced clear visualization, forming 12 band patterns that were formed by six bands which was different migrating direction to the anode pole (positive) and catode pole (negative). The dendrogram in this study showed that 50 individuals of ramin were clustered into two main separated groups at the level of 47% similarity coefficient. These data indicated that the genetic variation of ramin in PT.DRT was quite diverse.